Pre-hospital care in burn injury - Shrivastava Prabhat; Goel Arun (Indian Journal of Plastic Surgery)
The care provided to the victims of burn injury immediately after sustaining burns can largely affect the extent and depth of the wound. Although standard guidelines have been formulated by various burn associations, they are still not well known to public at large in our country. In burn injuries, most often, the bystanders are the first care providers. The swift implementation of the measures described in this article for first aid in thermal, chemical, electrical and inhalational injuries in the practical setting, within minutes of sustaining the burn, plays a vital role and can effectively reduce the morbidity and mortality to a great extent. In case of burn disasters, triage needs to be carried out promptly as per the defined protocols. Proper communication and transport from the scene of the accident to the primary care centre and onto the burn care facility greatly influences the execution of the management plans